Modern studies of the Tuvan family: problem-thematic and methodological analysis - Rostovskaya, Tamara K.; Natsak, Organa D.; Yagodka, Nikolay N.; Yelamanova, Ainur S. (The New Research of Tuva, 2024)
The article provides a review and systematization of scientific publications on marriage and family issues in Tuva, published from 2000 to the present. It presents a distribution of academic works by year, research institutions (author affiliations), types, fields of study, and thematic research directions (historical-ethnographic, ethnopedagogical, gender studies, structural-demographic studies, studies on child socialization in various family types, and others). A significant increase in the number of publications has been observed since 2016, peaking in 2020. This trend is explained by the growing research interest in marriage and family issues, the introduction of new methods for studying families, and the organization of scientific conferences that stimulate publication activity. Among research and educational centers, the highest number of works was prepared at Tuvan State University, the Tuvan Institute of Humanities and Applied Socio-Economic Research under the Government of the Republic of Tuva, and the Institute of Philosophy and Law of the Siberian Branch of the Russian Academy of Sciences. The majority of publications are articles in scientific journals and conference proceedings, with only four monographs published over the period under consideration. Most publications are in the fields of ethnography, pedagogy (ethnopedagogy), and sociology. Comparative studies, which allow transformations to be viewed in the mirror of indicators from other Russian regions and ethnonational communities, are also of considerable scientific value. While noting the positive achievements and the promise of continued research, the authors highlight certain methodological shortcomings in the published results.